An Online Survey of Social and Demographic Determinants of Stress among Workers in Jakarta Province - Putri, Adella Delisa; Nurcandra, Fajaria; Utari, Dyah; Shaifuddin, Siti Norashikin Mohamad (Universitas Airlangga, 2025)
Introduction: Stress is related to the individual's psychological, physiological, and behavioral response to stressors. Many social and demographic determinants are probable causative factors of stress through a complex path. In Jakarta Province, a significant number of workers commute from surrounding cities, potentially exacerbating stress due to long travel times, job demands, and other related factors. This study aimed to determine social and demographic factors contributing to stress among workers in Jakarta Province. Methods: A cross-sectional online survey was conducted between October and December 2023 among 200 workers aged 15–65 years. Data were collected using a self-administered questionnaire via Google Form, distributed through snowball sampling on social media. The survey included the Perceived Stress Scale (PSS-10), Multidimensional Scale of Perceived Social Support (MSPSS), Social Capital Scale, UCLA Loneliness Scale, and Social Network Index (SNI). A backward stepwise linear regression was performed to identify significant predictors of stress. Results: This study found that the mean stress score among workers was 19.39, which indicated a moderate stress level. The model showed social support (ß=-0.13), social capital (ß=-0.90), age (ß=-0.07), income (ß=0.00), distance (ß=0.19) as predictors of stress among workers and also obtained an R-Square value 50.4%. Conclusion: Social support, social capital, age, income, and commuting distance significantly influence workers' stress levels in Jakarta Province. Enhancing workplace social support systems and promoting stronger social networks may help mitigate stress. Employers and policymakers should consider interventions such as flexible work arrangements and peer support programs to improve employee well-being